Optimal Planning of an Off-grid Electricity Generation with Renewable Energy Resources using the HOMER Software - Hossein Shahinzadeh; Gevork B. Gharehpetian; S. Hamid Fathi; Sayed Mohsen Nasr-Azadani (Institute of Advanced Engineering and Science, 2015)
In recent years, several factors such as environmental pollution which is caused by fossil fuels and various diseases caused by them from one hand and concerns about the dwindling fossil fuels and price fluctuation of the products and resulting effects of these fluctuations in the economy from other hand has led most countries to seek alternative energy sources for fossil fuel supplies. Such a way that in 2006, about 18% of the consumed energy of the world is obtained through renewable energies. Iran is among the countries that are geographically located in hot and dry areas and has the most sun exposure in different months of the year. Except in the coasts of Caspian Sea, the percentage of sunny days throughout the year is between 63 to 98 percent in Iran. On the other hand, there are dispersed and remote areas and loads far from national grid which is impossible to provide electrical energy for them through transmission from national grid, therefore, for such cases the renewable energy technologies could be used to solve the problem and provide the energy. In this paper, technical and economic feasibility for the use of renewable energies for independent systems of the grid for a dispersed load in the area on the outskirts of Isfahan (Sepahan) with the maximum energy consumption of 3Kwh in a day is studied and presented. In addition, the HOMER simulation software is used as the optimization tool.